2015
DOI: 10.1001/jamadermatol.2015.0250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dermatology and Allergy Guidelines for Atopic Dermatitis Management

Abstract: Comparison of different guidelines may ultimately augment knowledge of treatment strategies and enhance realization of biases in the understanding and management of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 14 publications
0
35
0
2
Order By: Relevance
“…In contrast, two RCTs by Hata et al and Sidbury et al found no significant improvement with supplementation of vitamin D (35,36) and a 2008 Cochrane review concluded that studies were of poor quality and too small to provide conclusive evidence for the benefit of vitamin D supplements in AD. Surprisingly, even the recent guidelines for vitamin D supplementation in AD are not clear; while the AAD notes that there are insufficient data to recommend it, the Joint Task Force on Practice Parameters (allergy and immunology groups) supports it (17,37). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, two RCTs by Hata et al and Sidbury et al found no significant improvement with supplementation of vitamin D (35,36) and a 2008 Cochrane review concluded that studies were of poor quality and too small to provide conclusive evidence for the benefit of vitamin D supplements in AD. Surprisingly, even the recent guidelines for vitamin D supplementation in AD are not clear; while the AAD notes that there are insufficient data to recommend it, the Joint Task Force on Practice Parameters (allergy and immunology groups) supports it (17,37). …”
Section: Discussionmentioning
confidence: 99%
“…If different specialists treat AD with varying strategies, different outcomes may be obtained . Recently, a review paper compared some AD guidelines . The AD guideline published by the American Academy of Dermatology (AAD) 2014 working group with those created by the 2012 Joint Task Force (JTF) on Practice Parameters representing the American Academy of Allergy, Asthma & Immunology showed notable differences.…”
Section: Dermatologists and Immune‐mediated Allergic Cutaneous Diseasesmentioning
confidence: 99%
“…For example, about the environmental factors to avoid, e.g. sports as well as irritant sunscreen, clothing, minimizing exposure to aeroallergens without testing, elimination diet with the use of food‐specific IgE antibody testing or food challenge test if results of the IgE testing are negative, the JTF support its avoidance whilst the AAD conclude that there is not enough evidence to recommend them . Also, a different approach concerns ‘atopy patch test’ as a predictive diagnostic tool for late‐phase clinical reactions to proteins.…”
Section: Dermatologists and Immune‐mediated Allergic Cutaneous Diseasesmentioning
confidence: 99%
“…Current literature supports the aggressive use of systemic agents in psoriasis to achieve maximum skin clearance, QoL, and patient satisfaction . A comparison of dermatology and allergy guidelines for AD management showed agreement for the use of systemic therapies in cases of recalcitrant AD, but no treatment goals were identified. We review the American Academy of Dermatology (AAD) guidelines for psoriasis and AD management to highlight important differences that could suggest variations in the conceptualization of disease severity and effect on QoL.…”
Section: Introductionmentioning
confidence: 99%